Optimizing Patient Registration Process through Online Admission Application: A Scrum Approach - Suwito Pomalingo; Fenina Adline Twince Tobing (Jurnal Bumigora Information Technology (BITe), 2023)
Background: The healthcare environment is dynamic and often changes rapidly, whether in terms of regulation, technology or patient needs. Handling these changes and iterations in a short period of time and without disrupting hospital operations is quite a challenge.Objective: The research was conducted with the aim of optimizing the patient registration process at Bahagia Hospital in Makassar through an online system.Methods: The focus of this research was the application of the Scrum method in developing the application. Various methods were employed in this study, including observation, literature review, and interviews to gather user requirements. In the application development process, a series of sprints comprising planning, execution, review, and retrospection stages were carried out. The resulting application was able to quickly respond to user needs and improve services for patients.Result: The test results showed a success rate of 90% in achieving sprints within the specified time frame, indicating that the team was able to meet the set targets in each sprint.Conclusion: The effectiveness of the Scrum method in developing this application was affirmed in this study, thus it can be utilized for future development of similar applications.